Effect of probiotic-derived metabolites on hormonal and metabolic profiles in women with polycystic ovary syndrome: a systematic review and meta-analysis - Maddirevula, Maneesh Kumar; Nelson, Vinod Kumar; Soliman, Mohamed; Alanazi, Bader Khalid; Hegazy, Ahmed M. S.; Baig, Habeeb Ali; Soliman, Amro M.; Alanazi, Mansour (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPolycystic ovary syndrome (PCOS) is a common endocrine–metabolic disorder linked to insulin resistance and hyperandrogenism. Gut microbiota–derived metabolites, including short-chain fatty acids (SCFAs), indoles, and bile acids, influence endocrine and metabolic pathways. Yet, no systematic review has specifically examined metabolite-targeted interventions in PCOS.ObjectiveTo assess the effects of probiotic-derived metabolite interventions on hormonal and metabolic outcomes in women with PCOS.MethodsFollowing PRISMA 2020 and a PROSPERO-registered protocol (CRD42025543210), we searched MEDLINE, Embase, Web of Science, Scopus, Cochrane CENTRAL, and two Chinese databases to May 2025 without language restrictions. Eligible studies were randomized or quasi-randomized controlled trials ≥8 weeks. Two reviewers independently screened, extracted data, and assessed risk of bias (RoB 2). Pooled analyses used random-effects models, and evidence certainty was appraised with GRADE.ResultsSeventeen trials (n = 1, 214 women) were included, testing synbiotics (6), probiotics (7), sodium butyrate (2), Akkermansia muciniphila (1), and an SCFA blend (1). Interventions significantly reduced total testosterone (MD −0.19 ng/mL, 95% CI −0.30 to −0.08), LH/FSH ratio (SMD −0.46; 95% CI −0.66 to −0.26), fasting insulin (MD −2.4 µIU/mL; 95% CI −3.9 to −0.9), and HOMA-IR (MD −0.49; 95% CI −0.78 to −0.19). HDL-C increased modestly (MD + 3.2 mg/dL; 95% CI + 0.7 to +5.6). Evidence certainty was moderate for insulin-related outcomes and low for sex-hormone outcomes.ConclusionSTargeting gut-derived metabolites, particularly with sodium butyrate and multi-strain synbiotics, improves hormonal and metabolic markers in PCOS. Larger multicenter RCTs with metabolomic confirmation are warranted to establish clinical translation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025543210.